Delegation and Public Pressure in a Threshold Public Goods Game: Theory and Experimental Evidence - Doruk Iris; Jungmin Lee; Alessandro Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2016)
The provision of global public goods, such as climate change mitigation and managing fisheries to avoid overharvesting, requires the coordination of national contributions. The contributions are managed by elected governments who, in turn, are subject to public pressure on the matter. In an experimental setting, we randomly assign subjects into four teams, and ask them to elect a delegate by a secret vote. The elected delegates repeatedly play a one shot public goods game in which the aim is to avoid losses that can ensue if the sum of their contributions falls short of a threshold. Earnings are split evenly among the team members, including the delegate. We find that delegation causes a small reduction in the group contributions. Public pressure, in the form of teammates' messages to their delegate, has a significant negative effect on contributions, even though the messages are designed to be payoff-inconsequential (i.e., cheap talk). The reason for the latter finding is that delegates tend to focus on the least ambitious suggestion. In other words, they focus on the lower of the two public good contributions preferred by their teammates. This finding is consistent with the prediction of our model, a modified version of regret theory.
Keywords: C72; C92; D81; H4; Q54; 330; Delegation; Cooperation; Threshold Public Goods Game; Climate Experiment; Regret Theory